Examining store atmosphere appraisals using parallel approaches from the aesthetics literature. Issue 9 (13th June 2019) - Murray, John; Teller, Christoph; Elms, Jonathan
ABSTRACT: Drawing on the aesthetics literature, this study examines how typicality, novelty, unity and variety help to explain consumers' aesthetic pleasure and approach/avoidance behaviours. Comparisons are made between consumers' perceptions of actual store designs in a recently remodelled fashion store and that of an older, established store prototype owned by the same retailer. The research findings establish how novelty, typicality and variety confer aesthetic pleasure and approach behaviours in-store atmosphere appraisals contexts where there is a limited introduction of novelty, with one established prototype. The findings also suggest that moderation effects explain that consumers who place a greater value on the importance of design evaluate the novelty and aesthetic pleasure association differently compared to consumers with less design value orientation.